KELIMPAHAN POPULASI DAN TINGKAT EKSPLOITASI IKAN TERUBUK (Tenualosa macrura) DI PERAIRAN BENGKALIS, RIAU - Efizon, Deni; Djunaedi, Otong Suhara; Dhahiyat, Yayat; Koswara, Bachrulhajat (Fakultas Perikanan dan Kelautan, Universitas Riau, 2012)
Fish terubuk (Tenualosa macrura) isone of thefive species terubukspecies in the world. This fish is a fish Bengkalis community pride,but thepopulation has fallensignificantly comparedto previousyears. Thisstudy aimed to examine the various aspects in view of abundance and exploitationrates of fish terubuk at this time.From the research results obtained in the waters of fish terubukBengkalis contained in two age groups of